Taxonomic and functional diversity of aquatic macroinvertebrate from natural forest as reference for streams health indicators in Lasolo Watershed, Southeast Sulawesi, Indonesia - NASARUDDIN NASARUDDIN; LAODE SABARUDDIN; KANGKUSO ANALUDDIN; LA BACO SUDIA (Society for Indonesian Biodiversity, 2023)
Abstract. Nasaruddin N, Sabaruddin L, Analuddin K, Sudia LB. 2023. Taxonomic and functional diversity of aquatic macroinvertebrate from natural forest as reference for streams health indicators in Lasolo Watershed, Southeast Sulawesi, Indonesia. Biodiversitas 24: 5523-5538. Macroinvertebrates are known to play a crucial role in nutrient recycling and serve as valuable stream degradation indicators. Therefore, this study aimed to examine the structural and functional diversity of macroinvertebrate communities as a reference for stream health indicators in tropical Sulawesi, Indonesia. Spatial sampling using a multi-habitat method was conducted between September 2021 and March 2022 in five streams connected to natural forest and three from drainage areas in dryland farming. Data on forest cover, physical-chemical variables, and macroinvertebrate samples were collected, while the species richness and diversity trends across streams were analyzed using individual rarefaction curves. In addition, the composition of macroinvertebrate functional group was also evaluated. The results showed that 2474 individuals belonging to 77 genera were recorded throughout the area. We found a reduction in taxa composition by comparing the reference and impacted stream at the genus, family, and order levels with approximate values of 83.1%, 74.07%, and 55.6%, respectively. At least seven significantly different potential metrics that differentiated between reference and the impacted ecosystem were found, including the number of family taxa (#family), the number of insect taxa (#insect), the number of Ephemeroptera-Plecoptera-Trichoptera taxa (#EPT), the number of scraper taxa (#scraper), as well as Shannon-Wiener diversity, Simpson Evenness, and Margalef Richness index. These metrics offer a strong method for assessing land use change and their impact on freshwater biodiversity, emphasizing the importance of conservation efforts in the ecosystem.